Nanocrystals for the parenteral delivery of poorly water-soluble drugs - Sun, Bo; Yeo, Yoon (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
Nanocrystals have drawn increasing interest in pharmaceutical industry because of the ability to improve dissolution of poorly water-soluble drugs. Nanocrystals can be produced by top-down and bottom-up technologies and have been explored for a variety of therapeutic applications. Here we review the methods of nanocrystal production and parenteral applications of nanocrystals. We also discuss remaining challenges in the development of nanocrystal products. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: PHASE-I TRIAL; TISSUE DISTRIBUTION; INTRAPERITONEAL DOCETAXEL; ORIDONIN NANOSUSPENSION; ANTITUMOR EFFICACY; EUDRAGIT RS100(R); TOP-DOWN; FORMULATION; PHARMACOKINETICS; PERITONEAL